Thermal Timoshenko beam system with suspenders and Kelvin–Voigt damping - Mukiawa, Soh Edwin; Khan, Yasir; Al Sulaimani, Hamdan; Omaba, McSylvester Ejighikeme; Enyi, Cyril Dennis (Frontiers in Applied Mathematics and Statistics, 2023)
In the present work, we consider a thermal-Timoshenko-beam system with suspenders and Kelvin-Voigt damping type, where the heat is given by Cattaneo's law. Using the existing semi-group theory and energy method, we establish the existence and uniqueness of weak global solution, as well as an exponential stability result. The results are obtained without imposing the equal-wave speed of propagation condition.